The Trends of Research in Compressed Natural Gas (CNG) Pressure Vessel Technology: An Overview - R. A., Bakar; Mohamad Fatasya, Othman; Asnul Hadi, Ahmad (Universiti Malaysia Pahang, 2008)
The present scenario of the world crisis: price of the fossil fuel has increased. Compressed natural gas (CNG) pressure vessel becomes important in NGV fuel driving system because demand in CNG base has increased and because it is cheaper and more environmental friendly. CNG pressure vessel is suitable for gas operated vehicles which can be made of fully metal, hoop wrapped with metal liner, fully wrapped with metal liner or fully composite with HDPE liner. Fully metal CNG pressure vessel is cheap but it is the heaviest of the pressure vessels compare to others. For lightweight application such as for trucks, buses and taxis, fully composite tanks are more suitable but it comes with a high price. So, many researchers had searched for the best solution to store high volume of CNG with lightweight and cheap material. Even though the aim is clear but the development of CNG pressure tank must follow the standard requirements to prevent failure and minimize the accident. In this paper, the trends of research by manufacturers, research organizations and universities have been analyzed to find the problems and difficulties regarding CNG pressure vessel. The result of the overview showed that all types of tanks had advantages and disadvantages. It depends on the sector and industry concerned which types of CNG tanks are suitable for their usage.